DEVELOPING A RUBRIC FOR THE EVALUATION OF READING PROGRAMS FOR JOHNSTON COUNTY SCHOOLS - Pearce, Thomas David (East Carolina University, 2015)
The Superintendent of Johnston County Schools requested a program evaluation rubric for the selection of core reading programs. This final reading evaluation rubric allows users to measure the six key components of an effective reading program and provides descriptors and examples of each key area. This study was conducted using the methodology of improvement science as an approach to improving practice. In this specific case, improvement of the practice of reading program selection through restructuring of the evaluation process and the development of an improved evaluation rubric. Improvement science is explicitly designed to accelerate learning –by-doing (Carnegie Foundation, 2014). The plan, do, study, act cycle was followed by stakeholders in the developing of the final reading rubric. Research and data results from local school professionals were analyzed to develop the rubric. The final rubric provides ten descriptors in each of the six essential areas of reading, as determine by stakeholders, and can be used as a check – off list to ensure the program of choice has as many research based components as possible. Stakeholders revealed, through the use of the rubric, that several reading programs being used by the county did not include all of the key components of an effective reading program as determined by the National Reading Panel of 2000. Results of the study indicate that the use of the developed reading rubric would establish a standardized program evaluation process by reducing the number of programs that do not meet the criteria for program effectiveness.
Keywords: Reading rubric; Improvement science; Literacy programs--North Carolina--Johnston County--Evaluation; Reading--North Carolina--Johnston County